A Review Study on Reasons for Large Class Sizes in Tertiary Institutions in Nigeria - Ogunode, Niyi Jacob; Edinoh, Kingsley; Ewhe, Peter Okpunukpang (Indonesian Journal Publisher, 2024)
This paper discussed the reasons for large class sizes in tertiary institutions in Nigeria. Secondary data was used in the paper. Data were collected from print and online publications. The paper presented poor implementation of academic brief, poor implementation of carrying capacity, corruption, inadequate infrastructural facilities, shortage of academic staff, project abadonment, inadequate tertiary institutions and political influence asreasons for large class sizes in tertiary institutions in Nigeria. Based on this findings, the paper recommended increment in budgetary allocation of tertiary institutions employment of adequate academic staff and provision of adequate infrastructural facilities.